1985
DOI: 10.1021/bi00323a018
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen exchange of lysozyme powders. Hydration dependence of internal motions

Abstract: The rate of exchange of the labile hydrogens of lysozyme was measured by out-exchange of tritium from the protein in solution and from powder samples of varied hydration level, for pH 2, 3, 5, 7, and 10 at 25 degrees C. The dependence of exchange of powder samples on the level of hydration was the same for all pHs. Exchange increased strongly with increased hydration until reaching a rate of exchange that is constant above 0.15 g of H2O/g of protein (120 mol of H2O/mol of protein). This hydration level corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 23 publications
7
43
1
Order By: Relevance
“…Hydration-induced mobility in a solid protein was demonstrated previously in lysozyme powder using the hydrogen exchange reaction (Schinkel et al, 1985). At the final stage of hydration, where the motion is most prominent, the degree of hydration is close to that in SSI crystals (41 vol%, Satow et al, 1973).…”
Section: Powdercsupporting
confidence: 60%
“…Hydration-induced mobility in a solid protein was demonstrated previously in lysozyme powder using the hydrogen exchange reaction (Schinkel et al, 1985). At the final stage of hydration, where the motion is most prominent, the degree of hydration is close to that in SSI crystals (41 vol%, Satow et al, 1973).…”
Section: Powdercsupporting
confidence: 60%
“…Such protection has been observed with lyophilized lysozyme powders. 23 The H-D exchange is further decreased with an increasing percentage of trehalose (Table II). This suggests that 20% trehalose (1 : 4 weight ratio of trehalose/protein) is insufficient to protect exchangeable amide protons and an increasing trehalose content (up to 1 : 1) increases the protection.…”
Section: Extent Of Solvent-exposed Protons Of Trehalose and Proteinsmentioning
confidence: 94%
“…For example, the results of Fourier-transform infrared (FTIR) spectroscopic investigations of hen egg-white lysozyme were interpreted to indicate that lysozyme structure in either aqueous solution or the lyophilized state is the same (3)(4)(5)(6). This conclusion was supported by some hydrogen isotope-exchange studies (6,7) but contradicted by others (8). Raman (9)(10)(11) and solid-state NMR (12) studies have suggested significant (reversible) structural changes occurring in lysozyme upon lyophilization.…”
mentioning
confidence: 99%